High intensity interval training attenuate insulin resistance in diabetic rats accompanied by improvements in liver metabolism and spexin signaling - Kayvan Khoramipour; Najmeh Sadat Hosseini; Jennifer W. Hill; Karen Khoramipour; Kimya Khoramipour; Sergio Maroto Izquierdo; Simone Lista; Mona Saheli (Scientific Reports)
Abstract Spexin (SPX), a recently identified adipokine, shows potential in enhancing insulin sensitivity, offering promising implications for metabolic health. This study aimed to investigate the effect of 8 weeks of high intensity interval training (HIIT) on insulin resistance through liver gluconeogenesis, lipolysis, inflammation, oxidative stress, and lipogenesis in Type 2 diabetic rats with a special focus on the role of SPX. In this study, 28 male Wistar rats were divided into four groups: Healthy Control (CON), Diabetes Control (T2D), HIIT, and Diabetes+HIIT (T2D+HIIT). After diabetes induction (high-fat diet+streptozotocin), the exercise groups underwent an 8-week HIIT protocol. HOMA-β, HOMA-IR, QUICKI, fasting blood sugar, insulin, and SPX were measured in liver and serum. The expression of Galanin/2, FOXO-1, PGC-1α, G6Pase, PEPCK, CPT1A, AMPK, PPARα, ACC, FAS, SREBP-1c, SIRT-1, and inflammatory/antioxidant markers were analyzed in the liver. Our results showed that HOMA-β, QUICKI, insulin, and serum level of SPX levels were higher in T2D+HIIT than T2D group. Similarly, SPX, GALR2, FOXO-1, PGC-1α, CPT1A, PPARα, AMPK, and SIRT-1 levels were higher in the livers of rats in the T2D+HIIT than T2D group. However, HOMA-IR, PEPCK, G6Pase, ACC, FAS, and SREBP-1c levels were lower in T2D+HIIT than T2D group. Also, HIIT+T2D reduced inflammation and increased antioxidants, indicating an improved overall health status of the liver. HIIT benefits diabetic liver with reducing gluconeogenesis, inflammation, oxidative stress, and lipogenesis while increasing lipolysis. These improvements coincided with elevated hepatic SPX signaling and are associated with reduced insulin resistance. These findings suggest a potential association between HIIT induced SPX signaling modulation in liver and improving insulin resistance, though further mechanistic studies are required to confirm the causality.